2016
DOI: 10.1186/s12940-016-0107-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving health in cities through systems approaches for urban water management

Abstract: BackgroundAs human populations become more and more urban, decision-makers at all levels face new challenges related to both the scale of service provision and the increasing complexity of cities and the networks that connect them. These challenges may take on unique aspects in cities with different cultures, political and institutional frameworks, and at different levels of development, but they frequently have in common an origin in the interaction of human and environmental systems and the feedback relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 44 publications
2
29
0
1
Order By: Relevance
“…Also, the volumes of fecal sludge transported to the treatment plants would greatly increase. We expect that the increase in wastewater and fecal sludge, adequately treated, would translate into improved urban health and wellbeing for the city dwellers [46]. According to our calculations, OSS is the largest source of nitrogen reaching groundwater, a conclusion similar to that of other authors [35,36].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Also, the volumes of fecal sludge transported to the treatment plants would greatly increase. We expect that the increase in wastewater and fecal sludge, adequately treated, would translate into improved urban health and wellbeing for the city dwellers [46]. According to our calculations, OSS is the largest source of nitrogen reaching groundwater, a conclusion similar to that of other authors [35,36].…”
Section: Discussionsupporting
confidence: 82%
“…Unpublished work made by the authors has shown that the treatment capacity of the plant, as BOD and COD removal rates, is limited. Thus, it is clear that the largest percentage of wastewater and fecal sludge produced in the city is not adequately treated, which leads to serious environmental and health issues [44,46].…”
Section: Introductionmentioning
confidence: 99%
“…Integrated systems approaches involve interdisciplinarity, as complex city infrastructures comprise intersecting diverse natural, technical, and institutional dimensions [31]. Therefore, properly understanding these issues and the ways to solve them requires researchers and professionals from different academic and professional disciplines to provide input, exchange opinions, and learn from each other to discover new, creative solutions.…”
Section: Methods and Assessmentmentioning
confidence: 99%
“…On the other hand, water-washed diseases (hygiene-related) occur due to insufficient water supply for the maintenance of adequate hygiene. The pathogens are transmitted person-to-person through body contact [15,[32][33][34]. Insects, such as mosquitoes, which breed and feed in or near water cause vector-borne diseases (e.g., malaria and dengue).…”
Section: Water-related Infectious Diseases (Wrid)mentioning
confidence: 99%
“…Urban surface water systems are increasingly facing stress from pollution in most developing countries in Asia, Africa, and Latin America, as a result of land-use change, lack of wastewater treatment, and poor water quality monitoring [13][14][15]. Threats to human health, particularly the emergence and spread of water-related infectious diseases (WRID) and sanitation have been the focus of many research studies in South-East Asia and Sub-Saharan Africa; however, such studies focused less on the interactions between LULC and diseases [13,16,17].…”
Section: Introductionmentioning
confidence: 99%